Influence of selective laser treatment on thermal stability of Ti3AlC2 and Ti3AlC2/Cu powders - Krinitcyn, M.; Ragulina, M.; Firsina, I.; Travitzky, Nahum (Materials Letters, 2021)
Commercial Ti3AlC2 MAX phase powder and Ti3AlC2/Cu powder blends were used to obtain bulk materials using selective laser sintering/melting technique. In the present work, the influence of laser line energy on the stability of Ti3AlC2 composition was investigated. The structure of MAX phases was better maintained in composites with copper addition, forming a metal matrix composite with a copper matrix and Ti3AlC2 inclusions.
CRIS-Team Scopus Importer:2021-12-10
Keywords: MAX phases; Metal-ceramic composites; Selective laser melting; Selective laser sintering